2015
DOI: 10.7710/2159-1253.1078
|View full text |Cite
|
Sign up to set email alerts
|

An Interprofessional Education Nursing Home Dining Simulation Promotes Changes in Student Attitudes

Abstract: INTRODUCTION The purpose of this study was to assess changes in attitudes toward interprofessional collaborative competency attainment of undergraduate dietetics, gerontology/long term care administration, and occupational therapy assistant (OTA) students as a result of participating in a problem-based simulated nursing home dining experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…This develops communication and team working skills as well as enabling clinical competence and patient safety (Robertson andBandali 2008, Bridges et al, 2011). Arvin et al (2016) explored simulation, utilising problem-based scenarios. Their study showed attitudes of students had positively changed.…”
Section: Format Of Ipementioning
confidence: 99%
“…This develops communication and team working skills as well as enabling clinical competence and patient safety (Robertson andBandali 2008, Bridges et al, 2011). Arvin et al (2016) explored simulation, utilising problem-based scenarios. Their study showed attitudes of students had positively changed.…”
Section: Format Of Ipementioning
confidence: 99%